Relationship between Haematological Parameters and Cerebral Blood Flow Velocities in Sickle Cell Anaemia Children Seen At A Tertiary Hospital In Imo State (International Journal of Scientific Research and Management (IJSRM), 2025)
Background: Sickle Cell Anaemia (SCA) is a chronic haemolytic state associated with recurrent blood transfusions, infections and its attendant complications. The study compared the relationship between cerebral artery blood flow velocities(CBFV), steady state packed cell volume and white blood cell counts of male and female SCA children aged 2-16 years seen at Federal Teaching Hospital Owerri, Imo state. Methods: Transcranial Doppler ultrasound, haematology test(Packed cell volume and white blood cell count) were done for SCA children that attended the sickle cell specialist clinic of the hospital between April and September 2023. Results: A total of 102 subjects were screened within the study period. The mean packed cell volume was statistically significantly lower in males than females (p= 0.010). There was no difference in the mean white cell count in both genders. Abnormal CBFV was found in17.6% of subjects Conclusion: The prevalence of abnormal cerebral blood flow velocity in SCA children is 17.6%. Identification of subjects at risk for a CVA helped in primary prevention by prompt therapy institution. Keywords:Sickle cell anaemia, cerebral artery blood flow velocities packed cell volume, white blood cell count.